Peningkatan Kemampuan Pelafalan Huruf Hijaiyah Anak Melalui Media Permainan Ular Tangga: PTK Di Raudhatul Athfal Al-Ikhlas Pondok Ranggon Jakarta Timur - Diva Elviana; Khairil Ikhsan Siregar; Sadullah Sadullah (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research is intended to analyze the use of the hijaiyah snakes and ladders game media to improve the pronunciation ability of hijaiyyah letters in children aged 5-6 years. This research was conducted at Raudhatul Athfal Al-Ikhlas with the subjects being all Medina class students. This type of research is included in Classroom Action Research (PTK). This research was carried out in 3 cycles, each cycle containing four stages, namely: planning, acting, observing and reflecting. The subjects in this study were 12 children, including 7 boys and 5 girls. The data collection technique in this research was observation, and the results of the researcher's data analysis showed successive increases from pre-cycle, cycle I, cycle II to cycle III. In the pre-cycle there was 1 child with a percentage (8.3%) whose abilities met expectations but 0 children had very good abilities, in the first cycle there were 2 children with a percentage (16.6%) whose abilities met expectations and 3 children (25%) who very good abilities, then in cycle II there was quite a good increase, namely 4 children with a percentage (33.3%) who had abilities as expected and 5 children (41.6%) who had very good abilities, until the peak of increase was in cycle III with data on 4 children (33.3%) whose abilities met expectations and 7 children with a percentage (58.3%) including children with very good abilities. From the data that has been obtained, the author can conclude that the use of the hijaiyah snakes and ladders game media can improve the ability to pronounce hijaiyah letters in young children aged 5-6 years at Raudhatul Athfal Al-Ikhlas Pondok Ranggon, East Jakarta.